Projeto conceitual de uma cadeira inteligente para usuários com cifoescoliose - Yaçana Maria da Costa Soares Sousa Lima (2021)
Kyphoscoliosis is a columnar pathology that associates kyphosis and scoliosis. When not properly treated, it generates deformities in the trunk, cardiorespiratory changes and pain according to the severity of the deformation. Individuals with kyphoscoliosis find dificult to retain in a confortable sitting position, as current chairs do not have adequate support surfaces. The objective of this research was to elaborate a conceptual project of an inteligent chair to improve the confort and decrease the pain of people with kyphoscoliosis. The methodology was divided into three stages: elaboration and application of online questionnaries; definition of the parameters and normative requirements for the backrest and later for the seat. This research resulted in the development of a chair with a new concept on its back, in which telescopic hydraulic actuators arranged horizontally and in line were inserted. In each line the actuators where interconnected, transmitting the strength received from the prominent part of the gibosity and creating an adaptative acommodation surface. As for the seat, a conceptual project was developed to capture the pressure distribuition on this surface, in order to inform and educate the user about his posture when using the chair. Conclude that the project followed the premisses raised in relation to technical and scientific recommendations for comforty and safety. In addition, with the development of this assistive thechnology in the form of an smart chair, more people will be able to be included in the academic and professional environment everyday.